Punishing Women: The Promise and Perils of Contextualized Sentencing for Aboriginal Women in Canada - Williams, Toni (2007)
This article examines the failure of Canadian sentencing reforms to remedy the over-incarceration of Aboriginal woman through exploration of a sentencing methodology that judges may employ to give effect to the reforms: the social contextualization of women's lawbreaking. Social context analysis developed as a critique of how the state controls and punishes women and as a way to expose failures of justice. More recently, commentators have suggested that the insertion of social context analysis into the sentencing process might allow courts to find new and more robust justifications for lowering the penalties they impose on women lawbreakers from marginalized communities. This article also considers whether the emergence of risk as a rationale for penal intervention and control has made it more difficult for judges to realize the promise of contextualized analysis as a foundation for less harsh sentencing of Aboriginal women